2012
DOI: 10.1111/j.2042-3306.2011.00476.x
|View full text |Cite|
|
Sign up to set email alerts
|

Parturition, dystocia and foal survival: A retrospective study of 1047 births

Abstract: SummaryReason for performing study: An understanding of the normal events of foaling, causes of dystocia and clinical outcomes is important for equine practitioners. Objectives: The goals of the present study were to: 1) evaluate factors that influence gestation length; 2) report duration of Stage II labour; 3) determine the frequency of dystocia and premature placental separation; and 4) determine the relationship between problems at foaling and foal survival. Materials and methods: Foaling records of 1047 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
79
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 15 publications
(32 reference statements)
7
79
2
8
Order By: Relevance
“…These results differ from the majority of data for different breeds, in which the gestation length for colts was longer than that for fillies (Bos and Van Der Mey, 1980;Davies Morel et al, 2002;Pérez et al, 2003;Valera et al, 2006;Satué et al, 2011a b;Aoki et al, 2012;McCue and Ferris, 2012). Only few publications were not able to detect a significant influence of gender on the length of gestation (Campitelli et al, 1982;Valente et al, 2006), as it was found in our study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These results differ from the majority of data for different breeds, in which the gestation length for colts was longer than that for fillies (Bos and Van Der Mey, 1980;Davies Morel et al, 2002;Pérez et al, 2003;Valera et al, 2006;Satué et al, 2011a b;Aoki et al, 2012;McCue and Ferris, 2012). Only few publications were not able to detect a significant influence of gender on the length of gestation (Campitelli et al, 1982;Valente et al, 2006), as it was found in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Allen et al (2002), Davies Morel et al (2002 and Galvin and Corley (2010) obtained a mean of 338 ± 6.9, 344.1 ± 0.49 and 340.03 days of gestation for Thoroughbred mares, respectively, with a minimum of 312 and a maximum of 383 days. McCue and Ferris (2012) found a gestation mean of 341 ± 0.3 days in Thoroughbreds and QHs. Even when comparing the same breeds, a wide variation in gestation length is found, as can be observed in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that age of mares significantly influenced length of gestation. Although, a negative correlation between the age of mares and gestation length was reported, young mares have longer gestation than old mares [1] .…”
mentioning
confidence: 99%
“…However the maximal incidence was observed between 10 pm and 11 pm. Also a majority (52.8%) of mares foaled at night between 8 pm and 2 am [1] . E-mail: nsvahedi@yahoo.com…”
mentioning
confidence: 99%
See 1 more Smart Citation